Cultivating a Green Organizational Culture in Islamic Schools: The Central Role of Teacher's Akhlak (Ethics) and Exemplary Modeling - Niken Ristianah; M. Munir; Juni Iswanto; Akhmat Fanani Ridho; Toha Ma'sum; Syaiful Muda'i; M. Burhanuddin Ubaidillah (PT. Lembaga Penerbit Penelitian Nusantara, 2024)
This study investigates the formation and sustenance of a Green Organizational Culture within Islamic schools, focusing on the pivotal role of teachers' akhlak (ethical character) and their exemplary behavior (qudwah hasanah) as the primary drivers. A Green Organizational Culture is defined as a shared set of values, beliefs, and practices that prioritize environmental stewardship, sustainability, and ecological responsibility as integral to the school's identity and daily operations. Employing an ethnographic case study approach, this research was conducted at two Islamic secondary schools recognized for their proactive environmental programs. Data were gathered through prolonged observation, in-depth interviews with teachers and students, and analysis of school artifacts. Findings reveal that teacher akhlak—manifested as personal environmental mindfulness, consistency between words and actions, and moral motivation rooted in Islamic teachings—is the cornerstone for authentic cultural change. Teachers who embody green values act as transformative agents, legitimizing environmental norms, inspiring student imitation, and embedding sustainability into the hidden curriculum. The study concludes that institutional green policies are insufficient without the cultivation of akhlak-based environmental ethics among educators. It proposes a model of